Topology Architecture and Routing Algorithms of Octagon-Connected Torus Interconnection Network - Youyao Liu; Lidong Xing; Xin Zhou (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Two important issues in the design of interconnection networks for massively parallel computers are scalability and small diameter. A new interconnection network topology, called octagon-connected torus (OCT), is proposed. The OCT network combines the small diameter of octagon topology and the scalability of torus topology. The OCT network has better properties, such as small diameter, regular, symmetry and the scalability. The nodes of the OCT network adopt the Johnson coding scheme which can make routing algorithms simple and efficient. Both unicasting and broadcasting routing algorithms are designed for the OCT network, and it is based on the Johnson coding scheme. A detailed analysis shows that the OCT network is a better interconnection network in the properties of topology and the performance of communication.